AB1025 Chronic Recurrent Multifocal Osteomyelitis (CRMO): The Importance of an Accurate Differential Diagnosis. (9th June 2015) - Giani, T.; Capirchio, L.; Marino, A.; Bertini, F.; Mauro, A.; Simonini, G.; Pagnini, I.; Cimaz, R.
Abstract : Background: CRMO is a rare auto-inflammatory disorder, characterized by pain related to the presence of multifocal sites of sterile bone inflammation. CRMO is a diagnosis of exclusion established by clinical presentation, imaging studies, and culture-negative bone biopsy. Objectives: To compare 2 clinical cases with very similar clinical and radiological presentation but different diagnosis and outcome. Methods: Case 1. MM is a 11-year-old boy presented with a 4-months history of progressive left-clavicle pain associated with fever and good response to non-steroidal anti-inflammatory drugs (NSAIDs). Clinical examination revealed right supra-clavicle lymphadenopathy, and functional limitation of left arm with pain elicited by left clavicle palpation. Laboratory tests showed increase of inflammatory markers but normal complete blood count and LDH levels. Chest X-ray and abdominal ultrasonography were negative. Left clavicle MRI was compatible with osteomyeltis and empiric antibiotic therapy was started with clinical improvement. Three months later the patient presented with pain at right shoulder and arm, fever and nocturnal awakenings associated with persistent lymphoadenopathy. Inflammatory markers were increased and infections were excluded. Elbow X-ray and ultrasonography resulted negative as well as bone marrow aspirate. Bone-scintigraphy showed multiple sites of uptake and whole-body MRI showed multiple bone lesions located on both scapulae, clavicles, upper limbs, vertebrae (D5-11), and sternum. A diagnosis of CRMO was hypothesized. Case 2. LP presented at the age of 15 y with lumbosacral pain worsened with back movements, load lifting, and running, and present also at night. NSAIDs therapy was started, with partial improvement. Laboratory tests revealed slight increase of inflammatory markers, while X-Ray of the pelvis and the lumbosacral spine was normal. As an infectious form was initially suspected, broad-spectrum intravenous antibiotic therapy was administered. Whole-body MRI showed multiple bone lesions of the left femur, right sacrum and spine (L4, D12), findings confirmed by bone PET. Bone marrow aspirate excluded the presence of blast cells and extrinsic infiltration. Results: In order to obtain a definitive diagnosis bone biopsies were performed in both cases. In Case 1 bone histological examinations revealed lymphoid cells proliferation, and the diagnosis of B-cell lymphoblastic leukemia/lymphoma was confirmed by histological findings on lymph node biopsy. In Case 2 bone biopsy and histological examination showed lympho-histiocytic infiltrate without neoplastic cells. In the hypothesis of CRMO naproxen therapy was administered for 3 months, followed by clinical and radiological improvement. Conclusions: In these two cases clinical and radiological (especially whole-body MRI findings) presentations were very similar, and the diagnosis was possible only with histology. Moreover, in Case 2 bone lesions detected with MRI had typical location and findings attributable to autoinflammatory-bone disorders and the patient had a good response to therapy with NSAIDs, unlike Case 1. These two cases point out the difficulties and the caution to correctly diagnose a rare autoinflammatory bone disease. Disclosure of Interest: None declared